The Roles of Living Place Environment and Comorbidities Status on The Incidence of COVID-19: a study at health care facility of Lampung University - Latifah Widya Ningrum; Evi Kurniawaty; Khairun Nisa Berawi; Bainah Sari Dewi; Asep Sukohar; Samsul Bakri (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
Almost two years novel coronavirus (COVID-19) since first reported in the city of Wuhan, China classified as a pandemic. World Health Organization (WHO) has classified this disease as a pandemic with more than two hundred thousand active cases and more than eight thousand deaths in the world, as on eleven March 2020. The Purpose of this research to determine the roles of living place environment and comorbidities on the incidence of COVID-19. Method in this research is cross sectional and using quantitative research, which uses secondary data at health facilities from University of Lampung. Sample in this research using the Isaac & Michael test, obtained 186 samples with purposive sampling technique. The results of the logistic regression test, the result of age with OR value 2,057, B value = 0,721, p-value 0,039 in the health condition the OR value is 0,430, B value is 0,844, p-value is 0.019, history of hypertension comorbid OR = 9,123 with B value = 2,211, p-value 0,009 and diabetes comorbid OR = 5,551, B value = 1,714, p-value 0,049 and living place environment OR value = 1,983 and B value = 0,685, p-value is 0,044 they are have p-value less than 0,05 the meaning is age, health condition, comorbid history, and a person's living place environment have a significant effect on the incidence of COVID-19. The conclusion of this study reports that prevalence of productive age, poor health conditions, history of comorbidities hypertension and comorbidities of diabetes as well as the status of densely populated living place environment have a higher chance of contracting COVID-19 infection.